Efektivitas Foot Massage dan Tehnik Benson terhadap Penurunan Tekanan Darah pada Penderita Hipertensi di RS Bhayangkara Lemdiklat Polri - Maidah Awaliah; Tri Mochartini (Malahayati Nursing Journal, 2022)
ABSTRACT Hypertension is referred to as The silent killer often occurs without complaints because the patient does not realize he has hypertension, only to realize it after complications occur. Foot Massage and Benson's technique are non-pharmacological ways to lower blood pressure. Effectiveness of Foot Massage and Benson's technique on reducing blood pressure in patients with hypertension at Bhayangkara Hospital Lemdiklat Polri in 2022. Quasi-experimental, pretest-posttest control group design.Technique Purposive Sampling. Consists of 3 groups: Foot Massage, Benson Technique and a combination of Foot Massage and Benson Technique. The sample is 30 respondents. Paired sample t-test in 3 groups Sig-(2-tailed) 0.000 0.05. The combination of Foot Massage and Benson's technique is more effective with an average difference of 12.00 Systole Pre-Post Test and Diastole Test 6.60. There is the effectiveness of Foot Massage and Benson's Technique on Reducing Blood Pressure in Hypertension Patients at Bhayangkara Lemdiklat Police Hospital in 2022. Keywords: Hypertension, Foot Massage, Benson Technique  ABSTRAK Hipertensi disebut sebagai the silent killer sering terjadi tanpa keluhan karena penderita tidak menyadari dirinya menyandang hipertensi, baru disadari setelah terjadi komplikasi. Foot Massage dan Tehnik Benson cara non farmakologis untuk menurukan tekanan darah. Mengetahui Efektivitas Foot Massage dan Tehnik Benson Terhadap Penurunan Tekanan Darah pada Penderita Hipertensi Di RS Bhayangkara Lemdiklat Polri Tahun 2022. Quasi eksperimen, pretest – posttest control group design. Tehnik Purposive Sampling. Terdiri dari 3 kelompok : Foot Massage, Tehnik Benson dan perpaduan antara Foot Massage dan Tehnik Benson. Sampel sebanyak 30 responden. Uji Paired sample t-test pada 3 kelompok Sig-(2-tailed) 0,000 0,05. Perpaduan antara Foot Massage dan Tehnik Benson lebih efektif dengan selisih rata-rata Sistole Pre-PostTes 12,00 dan Diastole Pre- PostTes 6,60. Ada efektivitas Foot Massage dan Tehnik Benson Terhadap Penurunan Tekanan Darah pada Penderita Hipertensi Di RS Bhayangkara Lemdiklat Polri Tahun 2022. Kata Kunci: Hipertensi, Foot Massage, Tehnik Benson